Toward Automated Enzymatic Glycan Synthesis in a Compartmented Flow Microreactor System. Issue 19 (13th August 2019) - Heinzler, Raphael; Fischöder, Thomas; Elling, Lothar; Franzreb, Matthias
Abstract: Immobilized microfluidic enzyme reactors (IMER) are of particular interest for automation of enzyme cascade reactions. Within an IMER, substrates are converted by paralleled immobilized enzyme modules and intermediate products are transported for further conversion by subsequent enzyme modules. By optimizing substrate conversion in the spatially separated enzyme modules purification of intermediate products is not necessary, thus shortening process time and increasing space‐time yields. The IMER enables the development of efficient enzyme cascades by combining compatible enzymatic reactions in different arrangements under optimal conditions and the possibility of a cost‐benefit analysis prior to scale‐up. These features are of special interest for automation of enzymatic glycan synthesis. We here demonstrate a compartmented flow microreactor system using six magnetic enzyme beads (MEBs) for the synthesis of the non‐sulfated human natural killer cell‐1 (HNK‐1) glycan epitope. MEBs are assembled to build compartmented enzyme modules, consisting of enzyme cascades for the synthesis of uridine 5′‐ diphospho‐α‐ d ‐galactose (UDP‐Gal) and uridine 5′‐diphospho‐α‐d ‐glucuronic acid (UDP‐GlcA), the donor substrates for the Leloir glycosyltransferases β4‐galactosyltransferase and β3‐glucuronosyltransferase, respectively. Glycan synthesis was realized in an automated microreactor system by a cascade of individual enzyme module compartments each performing under optimal conditions. The products were analyzed inline by an MS‐system connected to the microreactor. The high synthesis yield of 96% for the non‐sulfated HNK‐1 glycan epitope indicates the excellent performance of the automated enzyme module cascade. Furthermore, combinations of other MEBs for nucleotide sugars synthesis with MEBs of glycosyltransferases have the potential for a fully automated and programmed glycan synthesis in a compartmented flow microreactor system. Abstract :